EdTech for Special Educational Needs and Disabilities in Malawi: Setting the Research Agenda - Plaut, Daniel; Pitchford, Nicola; Humphrey, Catherine (2024)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13907321 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1067 ZenodoArchiveConcept: 13907320
Keywords: _r:AddedByMyEducationEvidence

Using EdTech to Support Learning Remotely in the Early Years. Rapid Literature Review of Evidence from the Global Response to Covid-19. - Korin, Astrid (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org This topic brief examines the literature on technology-based, remote approaches to supporting learning in the early years for children from birth to age five, identifying promising practices for using EdTech in early childhood education (ECE) in low- and middle-income countries (LMICs). It draws on the nurturing care framework, Principles for Digital Development, and effective pedagogical practices for ECE.
ZenodoArchiveID: 4746391 previousDOI: 10.5281/zenodo.4746391 previousDOI: 10.5281/zenodo.4664510 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4664510 10.5281/zenodo.4746391 2339240:CJNJNHNU 2405685:RTQ64R3P 2405685:TD3Y79BH
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

EdTech in Liberia: A Rapid Scan - Upadhyay, Arjun; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private sector partnerships, and digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive. The aim is to provide a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Liberia. This report is based primarily on desk research, with quality assurance provided by a country expert.
ZenodoArchiveID: 5652130 previousZenodoArchiveID: 3830953 previousshortDOI: 10/ghgk68 previousDOI: 10.5281/zenodo.3830953 shortDOI: 10/ghgk68 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3830953 10.53832/edtechhub.0033 10/ghgk68 2339240:XCBTX2XL 2405685:2HM2SBVM 2405685:FU7Z8QM7
Keywords: C:Liberia; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH

Minoritised Languages, Education, and Technology: Current practices and future directions in low- and middle-income countries - Zhao, Annette; Mitchell, Joel; Gasanabandi, Gentille; Ullah, Noor; Barnes, Katrina; Koomar, Saalim (EdTech Hub, 2024)
This article explores the current status and future directions of mother-tongue-based multilingual education (MTB MLE) and the use of technology in low- and middle-income countries (LMICs), focusing on the use of minoritised mother tongues. An initial literature review of available academic sources in multiple languages reveals a lack of evidence on the use of technology in MTB MLE across different countries, especially multilingual contexts with greater linguistic diversity. To understand the issue in greater detail and to offer recommendations informed by current practice, interviews and a collaborative workshop with four organisations with relevant educational technology (EdTech) initiatives were conducted. The analysis covers facilitating and limiting factors these organisations have encountered, and the potential positive impact on learners and society generally. We conclude by identifying practical, policy, and research priorities for multilingual education and educational technology in general.
ZenodoArchiveID: 7267302 ZenodoArchiveConcept: 7267301 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7267302 10.53832/edtechhub.0127 2339240:V7ARHU93 2405685:GBBGHCBH 2405685:QADQUWU3 2405685:UTTZNZ24
Keywords: _r:AddedByZotZen